CURES: Ventura County Prescription Data - Kryshchenko, Alona; Flores, Cynthia; Alexander, Olivia; Nelson, Andrew; Sillas, Cynthia (CBR@CSUCI: An annual volume of community-based research, 2019)
CURES is a database of Schedule II, III and IV controlled substance prescriptions committed to the reduction of prescription drug abuse without affecting legitimate medical practice or patient care. Given a subset of data from California’s Prescription Drug Monitoring Program, we are focusing our efforts on Ventura County. With general patient information such as age, zip code of pharmacy where the prescription is filled as well as the prescription itself, we are analyzing our dataset in order to spot potential drug abuse. We are interested in finding a correlation, if it exists, between age, zip of pharmacy, or gender and how this relationship may affect prescriptions provided within our county. Through creating classification targets in order to simplify our given attributes of zip code of pharmacy, prescriptions provided, and drug strength, we aim to fit a set of attributes to a linear regression model.